History of Islamic Economics Thought III: Hisbah/Ihtisāb (Municipalism) Books - İçen, Hüseyin (RESEARCH CENTER ISLAMIC ECONOMICS-IKAM, 2023)
This book has provided awareness of the importance of hisbah, which is essential in maintaining social order and general morality. In the book, hisbah works have been examined in detail. In these works, many subjects such as state’s role in economic life, imports, jizyah, al-ribā (interest), al-ihtikār, cheat, embargo, narh, monopoly, waqf have been analyzed. The introduction of the hisbah literature will contribute to the establishment of the Islamic economic system and shed light on other studies in this area.